Pengaruh Kualitas layanan Terhadap Kepuasan Mahasiswa dengan Moderasi Budaya Organisasi dan Reputasi - Nilda Tri Putri; Budi Satria; Elita Amrina; Alfadhlani Alfadhlani (Universitas Katolik Parahyangan, 2021)
The purpose of this paper is to study the effects of service quality, organization culture and reputation on student satisfaction. This study uses 397 data collected from undergraduate students of Andalas University. The data is analyzed using structural equation modeling with SmartPLS 3.0, because of its ability to evaluate the measurement as well as the structural model. The results of this study show that service quality, organization culture and reputation significantly affect the student satisfaction. It is also found that service quality has the highest effect on student satisfaction, which means that increasing Andalas University service quality would significantly improve the satisfaction of its students. The results of this study also show that the organization culture nor reputation do not have moderating effect on the relationship between service quality and student satisfaction. This finding implies that organization culture nor reputation would not strengthen nor weaken the relationship between service quality and student satisfaction. Based on the findings, this study proposes several recommendations for University of Andalas to improve the satisfaction of its students.